When Is Carotid Angioplasty and Stenting the Cost-Effective Alternative for Revascularization of Symptomatic Carotid Stenosis? A Canadian Health System Perspective - Almekhlafi, M.A.; Hill, M.D.; Wiebe, S.; Goyal, M.; Yavin, D.; Wong, J.H.; Clement, F.M. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Carotid revascularization procedures can be complicated by stroke. Additional disability adds to the already high costs of the procedure. To weigh the cost and benefit, we estimated the cost-utility of carotid angioplasty and stenting compared with carotid endarterectomy among patients with symptomatic carotid stenosis, with special emphasis on scenario analyses that would yield carotid angioplasty and stenting as the cost-effective alternative relative to carotid endarterectomy. MATERIALS AND METHODS: A cost-utility analysis from the perspective of the health system payer was performed by using a Markov analytic model. Clinical estimates were based on a meta-analysis. The procedural costs were derived from a microcosting data base. The costs for hospitalization and rehabilitation of patients with stroke were based on a Canadian multicenter study. Utilities were based on a randomized controlled trial. RESULTS: In the base case analysis, carotid angioplasty and stenting were more expensive (incremental cost of $6107) and had a lower utility (−0.12 quality-adjusted life years) than carotid endarterectomy. The results are sensitive to changes in the risk of clinical events and the relative risk of death and stroke. Carotid angioplasty and stenting were more economically attractive among high-risk surgical patients. For carotid angioplasty and stenting to become the preferred option, their costs would need to fall from more than $7300 to $4350 or less and the risks of the periprocedural and annual minor strokes would have to be equivalent to that of carotid endarterectomy. CONCLUSIONS: In the base case analysis, carotid angioplasty and stenting were associated with higher costs and lower utility compared with carotid endarterectomy for patients with symptomatic carotid stenosis. Carotid angioplasty and stenting were cost-effective for patients with high surgical risk. BURSTBurden of Ischemic StrokeCAScarotid angioplasty and stentingCEAcarotid endarterectomyCRESTCarotid Revascularization Endarterectomy versus Stenting TrialEVA-3SEndarterectomy versus Angioplasty in Patients with Symptomatic Severe Carotid StenosisMImyocardial infarctionQALYquality-adjusted life yearsSAPPHIREStenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy